Updated recommendations from the Canadian National Consensus Meeting on HER2/neu testing in breast cancer - Hanna, W. (Multimed Inc., 2007)
Testing for her2/neu in breast cancer at the time of primary diagnosis is now the standard of care. Accurate and standardized testing methods are of prime importance to ensure the proper classification of the patient’s her2/neu status. A meeting of pathologists from across Canada was convened to update the Canadian her2/neu testing guidelines. This National her2/neu Testing Committee reviewed the recently published American Society of Clinical Oncology/ College of American Pathologists (asco/cap) guidelines for her2/neu testing in breast cancer. The updated Canadian her2/neu testing guidelines are based primarily on the asco/cap guidelines, with some modifications. It is anticipated that widespread adoption of these guidelines will further improve the accuracy of her2/neu testing in Canada.